X-RAY SPECTRAL MICROANALYSIS OF SINTERED SAMPLES FROM ELECTROEROSIVE COBALT-CHROMIUM POWDERS - Pykhtin, Alexey Ivanovich; Viktorovich, Ageev Evgeniy; Yurievich, Altuhov Alexander; Pavlovich, Emelianov Ivan (Journal of Applied Engineering Science, 2018)
To develop technologies for the reuse of alloy powders obtained from cobalt-chrome wastes and to evaluate the effectiveness of their use, complex theoretical and experimental studies are required. The main advantage of the proposed technology is the use of waste as raw materials, which is much cheaper than the pure components used in traditional technologies. The purpose of this work was to perform X-ray spectral microanalysis of sintered samples from cobalt-chrome powders obtained for additive technologies by electroerosive dispersion. For the implementation of the planned studies, wastes of the cobalt-chrome alloy of the brand KHMS "CELLIT" were chosen. For the production of cobalt-chrome powders, a device for electro-erosive dispersion of conductive materials was used. As a working fluid, butyl alcohol was used. The powders are consolidated by the method of spark plasma sintering using the system of spark plasma sintering SPS 25-10. Using the energy-dispersive X-ray analyzer from EDAX, built into the scanning electron microscope QUANTA 200 3D, spectra of characteristic X-ray radiation were obtained at various points on the surface of the sample. It has been experimentally established that Co and Cr are mainly contained in cobalt-chrome powder-alloys on the surface.